2007
DOI: 10.21273/hortsci.42.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Consumer Preferences and Interests in Developing a State Plant Promotional Program

Abstract: Two separate studies using intercept survey methodology were conducted to define the components of a state plant promotional program—Pennsylvania Gardener Selects (PGS)—based on consumer preference and appeal. The first study, conducted 6 and 7 Mar. 2003 at the Philadelphia Flower Show in Philadelphia, Pa., involved 243 Pennsylvanians. Objectives were to define current gardening-related shopping habits, sources of gardening information, motives and limitations for pursuing gardening, and history of pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Regarding origin, in‐state and domestic origins improved participants’ PL when compared to imported origins, supporting hypothesis 2. The origin coefficient estimates are consistent with previous research (Anella et al., ; Xie et al., ; Yue et al., ; Wehry et al., ). High VOC removal increased PL when compared to no VOC removal that is consistent with Solano ().…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding origin, in‐state and domestic origins improved participants’ PL when compared to imported origins, supporting hypothesis 2. The origin coefficient estimates are consistent with previous research (Anella et al., ; Xie et al., ; Yue et al., ; Wehry et al., ). High VOC removal increased PL when compared to no VOC removal that is consistent with Solano ().…”
Section: Resultssupporting
confidence: 91%
“…State promotion programs have been shown to improve plant sales by 81% (Anella et al., ) and increase consumer willingness‐to‐pay (WTP) by 10% (Collart et al., ). State promotion programs have successfully increased ornamental plant sales in Oklahoma (Anella et al., ) and Pennsylvania (Wehry et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these perceived benefits, consumers are willing to pay 10% to 170% more to obtain locally produced foods (Adams and Salois, 2010). However, few studies have addressed origin with ornamental plants and those studies have primarily focused on state-specific promotional campaigns, sales, and willingness to pay (Anella et al, 2001;Collart et al, 2010;Curtis and Cowee, 2010;Wehry et al, 2007;Winter et al, 2001;Yue et al, 2011a). Anella et al (2001) found the ''Oklahoma Proven'' plant campaign increased landscape plant sales by 81%.…”
Section: Plant Characteristics and Consumer Preferencesmentioning
confidence: 99%
“…Similarly, Curtis and Cowee (2010) determined Nevada homeowners were willing to pay a 14% premium for origin-certified (NevadaGrown) native plants. Local plants are perceived as being acclimated to the local environment and thus are more likely to survive (Curtis and Cowee, 2010;Wehry et al, 2007). State and local promotional programs positively impact consumer preferences for ornamental landscape plants, but do these benefits extend to indoor foliage plants?…”
Section: Plant Characteristics and Consumer Preferencesmentioning
confidence: 99%
“…The participants were sorted into nine segments in this study and it was determined that, similar to previous studies (Behe et al 2010, this segmentation was valuable in that it uncovered diff erences among the groups in ecopractices and preference for production practices, container types and production origin. Another study where clusters were determined based on information other than output from a conjoint analysis was Wehry et al (2007), in which select Pennsylvania gardeners were administered a survey at the Philadelphia Flower Show. Segments were divided based on participants' answers to four survey questions, uncovering their interest and history in purchasing locally-produced products, their product evaluations, and their perceived horticultural ability and knowledge.…”
Section: Introductionmentioning
confidence: 99%